An assessment on the skills in social studies course curriculum in Turkey - Eray Alaca (Intelektual Pustaka Media Utama, 2023)
The needs of individuals are increasing and diversifying in the rapidly changing world. Individuals cannot continue their lives in society through the only theoretical knowledge, and they also use the skills they have gained. In this regard, the social studies course has an important function in terms of where and how the skills will be used. The fact that the nature of the social studies course is a course in which the theoretical and practical information that prepares students for life are provided, has made it important to teach the skills in the social studies course compared to other courses. In this study, the skills included in the social studies course curriculum in Turkey were examined. In the study, it was observed that the skills were not directly included in the curriculum implemented until 2005. Therefore, the study was limited to the skills included in the social studies course curriculum implemented since 2005. In this study in the case study design, document analysis was applied, and the findings were subjected to descriptive analysis. Thus, it is purposed to reveal the change and transformation by determining the skills added and removed in the social studies course curriculum.